Inovasi Pembelajaran Batik Ramah Anak (Batik Simbut) di SDN Kwagean Wonopringgo Kab. Pekalongan - Cahyo, Andri Nur; Mursidah, Mursidah; Rachdantia, Dheasari; Dwirainaningsih, Yustiana (Indonesian Journal of Islamic Elementary Education, 2023)
Batik is Indonesia's noble culture and has been attached as an identity as well as national identity. This is important to do so that the Indonesian people do not lose their national identity in the midst of the swift onslaught of foreign cultures in the current era of globalization. The movement to preserve the local wisdom of batik culture must start as early as possible. Batik simbut innovation is one way to introduce batik culture to the younger generation, especially at an early age and elementary school. Batik simbut is child-friendly because it uses a kind of cold paste as a substitute for the function of hot wax. This study discusses learning innovation of Batik simbut that is applied to the Penguatan Profil Pelajar Pancasila program at SDN Kwagean. The method used is descriptive qualitative. The findings from this study are (1) the application of Batik simbut is considered safer, so it can minimize the risk of accidents due to hot nights for students. (2) The application of learning innovations of child-friendly batik in the P5 project is very appropriate and strategic as an effort to build students' curiosity and inquiry abilities through cultural exploration and local wisdom. This is expected to be an effort to strengthen the nation’s character as early as possible.